Index Kepuasan Pengguna Layanan terhadap Pelayanan pada Kantor SAMSAT Makale, Kabupaten Tana Toraja - Limbongan, Mey Enggane; Oktajayanice, Wildalend (UKI Toraja Press, 2022)
This study aims to determine the service user satisfaction index towards services at the Makale SAMSAT office, Tana Toraja Regency. The research method uses quantitative descriptive analysis with the calculation of the Community Satisfaction Survey (SKM) at PERMENPAN RB Number 14 of 2017. The data collection techniques were carried out using observation, questionnaires and documentation techniques. The results of the study were based on the calculation of the Community Satisfaction Survey of the 9 elements that had the highest IKM value, namely facilities and infrastructure with an SKM value of 8.4 and an IKM conversion value of 85 in good category. While the element that has the lowest IKM value is the element of service costs/tariffs getting an SKM value of 2.773 and the IKM conversion value of 69.325 is in the poor category. Overall, the IKM value at the Makale SAMSAT Office service unit is 3.093 with an IKM conversion value of 77.85 which means the service quality at the Makale SAMSAT Office, Tana Toraja Regency is at the 'B' or